Estimasi Potensi Cadangan Air Tanah Dengan Metode Persamaan Darcy di Desa Pilomonu, Gorontalo - Sugianti, Komang; Zainuri, Ahmad; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2022)
This research aims  to know  the  prediction   of potential   for  groundwater reserves.   The  research method  applies  surface  geological mapping  and subsurface  data  collection  with  the 200-span   Schlumberger configuration   geoelectric  method.  The  stratigraphy of the research   area  is  sorted  from  old  to  young,  the  first  is  the  granodiorite   unit,  the sandstone   unit,  and  alluvial   units   are  deposited   inconsistently.   The  geological structure working in the research area has a dominant northwest-southeast direction. The  direction  of. groundwater flow  follows the topography of the  research area, whicb is flowing from the north to the south, where the elevation  of the norlh js higher than the eJevation of the south. The aquifer characteristics in the research area can be divided  into two based  on the mterpretation  of geoelectric  inversion,  such as shallow  aquifer with material  in the  form of sand  and  deep  aquifer with  sand  and gravel material. Prediction  of the  potential  for  groundwater   reserves   is  obtained  from  the interpretation   of geoelectric  data  and data  from  the  calculation  of the  groundwater level in the research area by observing the. conditions  around the research area So, it is obtained a prediction  of potential  for shallow groundwater reserves is 360.444 m3/day or equivalent to  360,444   liters/day,  and  the  prediction   of poteptial   deep groundwater reserves is 66,520.476  m3/day or equivalent to 66:,520,476 liters/day.